Tinjauan Hukum Ekonomi Sayari’ah Tentang Jual Beli Melalui Jasa Go-Food - Sulthonuddin, Bung Hijaj; Sabani, Ai Mutmainah (STAI Al Musaddadiyah Garut, 2023)
The Go-food service feature in the Go-jek application is a buying and selling service between consumers and sellers through Go-jek driver intermediaries. The interest in studying Go-food services is that there are differences of opinion in the perspective of Islamic law regarding the validity of buying and selling using the service. The purpose of this study is to find out the buying and selling system through Go-food services, the mechanism of buying and selling through Go-food services in the Go-jek application, and to find out the perspective of Sharia economic law on buying and selling through Go-food services in the Go-jek application. This research is included in the type of qualitative research with data collection techniques used, namely interviews, observation, and documentation. From this data is analyzed through the stages of data reduction, data presentation, then conclusions. Based on the results of this study, it was found that the mechanism of buying and selling through Go-food services in the Go-jek application is basically the same as buying and selling online as usual. In the perspective of Islamic economic law, buying and selling through Go-food services is included in the Ba'i As-Salam contract, it can also use the istishna contract and the qardh contract. In addition, the sale and purchase has fulfilled the pillars and conditions of buying and selling and is in accordance with the principles of buying and selling, so that buying and selling through Go-food services in the Go-jek application can and is halal. Keywords : Sharia Economic Law, Buying and Selling, Gojek, Gofood